Manifestações do interlocutor nas produções textuais escritas no ensino fundamental - Franzoi, Rafaela de Cássia (2009)
Interlocutor's manifestations in written textual production in primary school classes are reported. The factor's importance, considered by Bakhtin (2003) as accountable for active responsive comprehension and one of the essential events for the undertaking of textual production, is analyzed. The following research question and its subdivisions have been suggested: In what manner the interlocutor's manifestations occur in written textual production? (a) Which are the factors that limit the interlocutor's influence in written textualproduction in the classroom? (b) How does the interlocutor's absence in the control of textual production manifests itself in the students' texts? Do the real and virtual interlocutor's notions affect and manifest themselves in the students' texts? Current research work tries to answer these questions foregrounded on the social and historical perspective on the study of language based on theories by Bakhtin/Volochinoc (1995), Bakhtin (2003) and Vygotsky (1988). It investigates the theoretic reflections on language, specifically the written language, its constitution and availability in discourse formation, since it is the social and historical product in social interaction through enunciations. Texts written by seventh-year students of a junior private primary school in the municipality of Marialva, PR - Brazil were analyzed. Although materials produced by nine students were collected, only three students were selected as samples. Results show that interlocutors are affected by the use of linguistic elements. Since the students do not delimit the interlocutor in the control of textual production, they have pinpointed other participants in the same enunciation. Further, the absence of the other's image provided means by which the students defined the class teacher as the real interlocutor, with the role of evaluator. This factor impaired the continuity of a dialogical process and active responsive comprehension. When the objective and the interlocutor, by whom mediation and explanation of the need to delimit the factors conditioning textual production was triggered, have been brought to the fore, the concern on how to produce an account, the discursive genre selected for the assignment, was detected. Since the students tried to comply with the delimitations exposed by the interlocutor to whom the written text was given, they adjusted the text according to the image of the other. They made their own the others' discourses which they appropriated, reworked and re-emphasized so that they could be given to the participant of the dialogic process. The students had naturalized the establishment of the dialogic process with the other through the written word.